IIUM Entrepreneurship Educators Module 1.0 - Mohd Shariff, Ros Aniza; Abu Samah, Mohd Armi; Abdul Rahman, Rozailin; Harun Ismail, Ahmad Fahmi (Entrepreneurship Development Centre, IIUM., 2021)
IUM Entrepreneurship Educators Module 1.0 is a precise and comprehensive module created and intended to guide and accelerate the IIUM Entrepreneurship Educators professional knowledge and skills development. This module provides an extensive curriculum toward development of entrepreneurs' holistic skills and knowledge from basic level of entrepreneurship, social entrepreneurship, digital entrepreneurship to business tools such as Value Proposition Canvas.